Review of algorithms for automatic verification of off-line signatures - Vílchez-Fernández, Luis Enrique (2017)
Nowadays, the signature is one of the most accepted badges for personal identification. Its inclusion is mandatory in documents such as bank checks, contracts, credit cards, among other public and private documents. However, the signature has become an attractive target for counterfeiting and, consequently, for fraud. For this reason, research has been carried out on automated signature recognition and state-of-the-art studies that are now required to be updated, since the most comprehensive work dates back to 2008 and in the following years further research has been carried out. The present work focuses on the comparative study of verification techniques of signatures offline from the point of view of efficiency and accuracy to verify the person’s authenticity. The research methodology used considers the procedure proposed by Kitchenham, which has been adapted, and involves the phases of planning, development and reporting of the review.